Real-space simulation of cyclic voltammetry in carbon felt electrodes by combining micro X-ray CT data, digital simulation and convolutive modeling. (1st September 2020) - Tichter, Tim; Andrae, Dirk; Schneider, Jonathan; Gebhard, Marcus; Hilger, André; Manke, Ingo; Roth, Christina
Abstract: A novel four-step strategy for real-space simulation of cyclic voltammetry (CV) at carbon felt electrodes is presented, circumventing the diffusion domain approximation approach used so far for CV simulation at porous electrodes. At first, the three-dimensional template of the internal electrode structure is constructed from micro X-ray tomography measurements. Subsequently, by exploiting the Douglas–Gunn modification of the three-dimensional Crank–Nicolson algorithm to Cottrellian boundary conditions, the mass transfer controlled current of this "true" network is obtained. Based on this current, the third step is to compute the mass transfer functions related to the electrode under investigation by an inverse convolution algorithm. In this manner, the spatial dimensionality of the system is reduced from three to one, resulting in significant savings in computation time. The fourth and final step is then to simulate CV experiments via classical convolution methods, featuring the great advantage that any degree of electrochemical reversibility, coupled homogeneous reactions, electrolyte resistances and double layer capacities can be implemented readily. As a proof of concept, the simulations are supported by experimental data acquired for the oxidation of VO 2+ in carbon felt electrodes.